Effect Of Receivables, Inventories, and Payables On Working Capital - Dian Oktavia; Menik Indrati (Publikasi Indonesia, 2021)
This study aims to analyze the effect of receivables, inventories, and payables on working capital. Receivables are measured by dividing total credit sales by the company's average receivables, inventories are measured by dividing the total cost of goods sold by the average inventory, and payables are measured by dividing the total purchases by the average trade payables. Firm size is measured by the logarithm of the company's total assets in year t, leverage is measured by dividing total debt by total equity, and profitability (ROA) is measured by the percentage of net profit after tax to total assets. The sample in this study was 30 companies, with 90 data. The object of research is a manufacturing company listed on the Indonesia Stock Exchange in 20 – 2019. The statistical methods used in this study are descriptive statistical analysis and inferential analysis which include classical assumption testing, multiple regression analysis, and hypothesis testing, using the SPSS program. The results of this study indicate that the receivables variable partially hurts working capital. Inventories partially have a positive effect on working capital. Debt partially does not affect working capital. The conclusion from the results of this study indicates that receivables, inventories, and payables affect working capital. The test results show that receivables have no partial effect on working capital, while inventory has a significant positive effect on working capital and debt does not partially affect working capital.